Elucidating the Role of Next Generation Immune Checkpoint Inhibitors in the Management of Philadelphia Chromosome-Negative Classic Myeloproliferative Neoplasms: A Comprehensive Literature Review - Yadav , Ruchi; Hakobyan, Narek; Wang , Jen C. (Advanced Concepts in Medicine and Medical Research Vol. 9, 2023)
The Philadelphia chromosome-negative (Ph-) myeloproliferative neoplasms (MPNs), encompassing essential thrombocythemia (ET), polycythemia vera (PV), and myelofibrosis (MF), represent a group of persistent and well-documented hematological disorders. These conditions are typified by aberrant proliferation of one or more hematopoietic cell lineages within the body’s stem cells, culminating in organomegaly and the emergence of constitutional symptoms. A plethora of research has substantiated that the etiology of these maladies is intricately linked to immune system dysregulation and chronic inflammation, both of which play pivotal roles. Recent advancements in oncological therapeutics, particularly in hematological malignancies, have been directed towards modalities targeting the immune system, the cytokine milieu, immunotherapeutic agents, and specialized immune therapies. Immune checkpoints, which are crucial regulators of T cell functionality within the tumor microenvironment (TME), include primary checkpoints such as programmed cell death-1 (PD-1)/programmed cell death ligand-1 (PD-L1), and cytotoxic T-lymphocyte antigen-4 (CTLA-4). Immune checkpoint inhibitor therapy (ICIT) revolutionizes cancer treatment by obstructing the inhibitory pathways in T cells. Despite the remarkable clinical achievements of ICIT, intrinsic tumor resistance remains a formidable challenge for oncologists, manifesting as suboptimal response rates in both solid tumors and hematological malignancies. A Phase II clinical trial (Identifier: NCT02421354) investigating the efficacy of nivolumab, a PD-1 blockade agent, in patients with post-essential thrombocythemia myelofibrosis, primary myelofibrosis, or post-polycythemia myelofibrosis was initiated but prematurely terminated due to adverse events and insufficient efficacy. Concurrently, a multicenter, Phase II, single-arm open-label study involving pembrolizumab in patients with primary thrombocythemia, post-essential thrombocythemia, or post-polycythemia vera myelofibrosis, who were ineligible for or had previously received ruxolitinib treatment, was conducted. This study concluded that while pembrolizumab administration was not associated with significant adverse events, it failed to elicit meaningful clinical responses, leading to its discontinuation after the initial stage. In light of these outcomes, the focus in immunotherapy has shifted towards novel immune checkpoints within the TME, such as lymphocyte activation gene-3 (LAG-3), T cell immunoglobulin and mucin domain 3 (TIM-3), T cell immunoglobulin and ITIM domain (TIGIT), V-domain immunoglobulin-containing suppressor of T cell activation (VISTA), and human endogenous retrovirus-H long terminal repeat-associating protein 2 (HHLA2). These are forming the foundation for the next generation of ICIT. The primary objective of this discourse is to highlight and explicate the importance of next-generation ICIT in the context of MPN. Specifically, this article seeks to investigate the potential of monoclonal antibodies as targeted immunotherapy and the development of vaccines targeting specific MPN epitopes, aiming to enhance tumor-related immune responses. It is projected that these immunotherapy-based therapeutic strategies will not only broaden but also refine the treatment spectrum for MPN patients. Preliminary investigations in our laboratory have revealed over-expression of MDSC and VISTA in MDSC, progenitor, and immune cells, underscoring the necessity for additional clinical trials employing next-generation ICIs in MPN management.